Eksplorasi Material Bubuk Mesiu dalam Proses Berkarya Seniman Cai Guo-Qiang - Dieni Nuraini; Abdusyukur Budiarvin Septiadi; Amanda Harmani; Farhan Deniansah; Ariesa Pandanwangi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Cai Guo-Qiang, a contemporary artist from China, creates works of art using gunpowder as a material. The purpose of this research is to find out the process of making paintings using gunpowder. The method used is a descriptive analysis method and a material exploration method that can generate heat. The conclusion of this study indicates that gunpowder can be used on the surface of iron plates, wood materials, and canvas surfaces by sprinkling gunpowder which generates heat on the surface of the area to be visualized and then igniting it using a match.